(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prastiyanto ME. 2021. Seeds extract of three Artocarpus species: Their in-vitro antibacterial activities against multidrug-resistant (MDR) Escherichia coli isolates from urinary tract infections (UTIs). Biodiversitas 22: 4362-4368. Multidrug-resistant (MDR)-E. coli is a major cause and has become a very serious problem in urinary tract infections (UTIs). As a result, it requires an antibacterial agent derived from biological materials. It has been reported that the seeds of three species of Artocarpus (A. heterophyllous, A. champeden, and A. camansi) have antibacterial properties against Methicillin-Resistant Staphylococcus aureus (MRSA). However, there are three other Artocarpus species in Indonesia, i.e., keledang (A. lanceipolius), tarra (A. elasticus), and terap (A. Odoratissimus) whose antibacterial property has not been investigated. To minimize the research gap, this study aims to determine the antibacterial activity of seed extracts of A. lanceipolius, A. elasticus, and A. odoratissimus against MDR-E. coli isolates of UTIs. Antibacterial activity was evaluated using the agar well diffusion assay. The microdilution method was used to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. The results revealed that the seed extracts of A. lanceipolius, A. elasticus, and A. odoratissimus have the potential as antibacterial agents against MDR-E. coli isolate of UTIs. A. elasticus seed extract shows the widest zone of inhibition in the range of 7.0-13.3 mm and the smallest MIC and MBC values ??of 6.25-12.5 mg/mL and 12.5-25 mg/mL, respectively. In conclusion, A. lanceipolius, A. elasticus, and A. odoratissimus seed extracts have the potential to be developed as antibacterial agents against UTI-causing MDR-E. coli. Further in vivo research and determining the mode of action of antibacterial activity are needed.